2018
DOI: 10.1002/slct.201801575
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and 3D‐QSAR of New Quinazolin‐4(3H)‐one Derivatives Containing a Hydrazide Moiety as Potential Fungicides

Abstract: A series of quinazolin‐4(3H)‐one derivatives containing a hydrazide moiety were designed, synthesized and characterized in detail via FT‐IR, 1H NMR, 13C NMR and HRMS spectra. The antifungal activities against Rhizoctonia solani (Rs) and Fusarium graminearum (Fg) were evaluated in vitro. The bioassay results indicated that most of the title compounds exhibited significant antifungal activities against Rs and Fg. Strikingly, the EC50 values of some title compounds against Rs are obviously superior to that of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…In this context, natural products have emerged as highly promising sources of lead candidates for use in small-molecule drug discovery . It has been shown that essential features of natural products are chemical diversity and diversity in biological functions, making natural product libraries favorable and attractive in drug discovery . Nonetheless, the paucity of these biologically active products in native plants and the challenges of extracting the target compounds from other metabolites with similar chemical properties have hindered research interests in this area .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, natural products have emerged as highly promising sources of lead candidates for use in small-molecule drug discovery . It has been shown that essential features of natural products are chemical diversity and diversity in biological functions, making natural product libraries favorable and attractive in drug discovery . Nonetheless, the paucity of these biologically active products in native plants and the challenges of extracting the target compounds from other metabolites with similar chemical properties have hindered research interests in this area .…”
Section: Introductionmentioning
confidence: 99%
“…indicated the reliable predictive accuracy of 3D‐QSAR models. [ 33‐36 ] Contour maps for the CoMFA and CoMSIA models were displayed in Figure 4. Actual and predicted pEC 50 values for the training set and test set were reported in Table 2, and the correlation plots of CoMFA and CoMSIA models were shown in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…The antifungal activities of the synthesized compounds were tested in vitro against R. solani , F. graminearum , B. cinerea and C. cinerea by a mycelium growth rate method, with carbendazim as the positive control. [ 33‐35 ] The tested fungal strains were provided by the Laboratory of Plant Disease Control, Nanjing Agricultural University. The target compounds with inhibition rates exceeding 50% at the concentration of 10 μg/mL were further tested for their antifungal inhibition rates at five different concentrations to calculate the corresponding EC 50 values.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations